Escherichia coli expressing chloroplast chaperones as a proxy to test heterologous Rubisco production in leaves - Buck, Sally; Rhodes, Tim; Gionfriddo, Matteo; Skinner, Tanya; Yuan, Ding; Birch, Rosemary; Kapralov, Maxim V; Whitney, Spencer M (Journal of experimental botany, 2023)
Rubisco is a fundamental enzyme in photosynthesis and therefore for life. Efforts to improve plant Rubisco performance have been hindered by the enzymes' complex chloroplast biogenesis requirements. New Synbio approaches, however, now allow the production of some plant Rubisco isoforms in Escherichia coli. While this enhances opportunities for catalytic improvement, there remain limitations in the utility of the expression system. Here we generate, optimize, and test a robust Golden Gate cloning E. coli expression system incorporating the protein folding machinery of tobacco chloroplasts. By comparing the expression of different plant Rubiscos in both E. coli and plastome-transformed tobacco, we show that the E. coli expression system can accurately predict high level Rubisco production in chloroplasts but poorly forecasts the biogenesis potential of isoforms with impaired production in planta. We reveal that heterologous Rubisco production in E. coli and tobacco plastids poorly correlates with Rubisco large subunit phylogeny. Our findings highlight the need to fully understand the factors governing Rubisco biogenesis if we are to deliver an efficient, low-cost screening tool that can accurately emulate chloroplast expression.